Protection of the chronic hypoxic immature rat heart during global ischemia - Karck, Matthias; Ziemer, Gerhard; Zöller, Max; Schulte, Steffen; Jürgens, Klaus Dieter; Weisser, Herwig; Haverich, Axel (The annals of thoracic surgery, 1995)
The benefit of cardioplegic cardiac arrest for the protection of immature myocardium is controversial. We therefore investigated the efficacy of (1) topical hypothermia alone, (2) slow cooling by coronary perfusion hypothermia, and (3) cardioplegic cardiac arrest for the protection of isolated immature rat hearts (28 days) during 8 hours of global ischemia at 10°C. The study was conducted in hearts from rats that were kept hypoxemic by lifelong exposure to simulated high altitude. Left ventricular function, endothelial function, the metabolic status, and the extent of myocardial injury were all assessed. Topical hypothermia provided superior protection in hypoxic hearts, with recovery of the maximum developed left ventricular pressure by 70.6% ± 18.0% (mean ± standard deviation) of its preischemic value (p < 0.01 versus slow cooling and versus cardioplegic protection). The same pattern of recovery was observed among control hearts. The degree of recovery of endothelial function after sole topical hypothermia measured 54% ± 36% in hypoxic hearts and 62% ± 37% in control hearts, but was not recordable in any of the other groups. Creatine kinase leakage and the myocardial high-energy content did not differ significantly among any of the groups. Rapid cooling by topical hypothermia alone provides superior protection in chronic hypoxic, immature rat hearts versus the protection conferred by slow cooling. St. Thomas' Hospital cardioplegic solution II does not afford additional protection. Endothelial injury caused by cold asanguineous perfusates, including cardioplegia, interferes with the recovery of vascular function, which, in turn, may limit mechanical function.